Patient Satisfaction in Functional Rhinoseptoplasty: The Role of Nonsurgical Factors - Antunes, Miguel Arede; Fernandes, Rita; Peça, Rita; Martins, Paulo; Luís, Leonel (Facial Plastic Surgery, 2025)
Functional rhinoseptoplasty (FRS) is a surgical procedure with both functional and aesthetic impacts, significantly affecting patients' quality of life. The influence of nonsurgical factors on FRS outcomes remains a debated topic in the literature. For instance, some authors deny the long-term impact of gender, age, inferior turbinectomy, or active smoking on the results. The rhinoplasty outcome evaluation (ROE) questionnaire is a useful tool for assessing patients' satisfaction once submitted to this surgery.To evaluate the subjective impact of nonsurgical factors on the long-term outcomes of FRS.The authors conducted a retrospective study of all patients who underwent FRS at a tertiary hospital between 2019 and 2023. Patients with less than 1 year of postoperative follow-up were excluded. The ROE questionnaire was used to quantify subjective surgical satisfaction. Various variables were analyzed, including previous nasal pyramid trauma, age, known hematologic pathology, psychiatric history, allergic rhinitis, smoking habits, and inferior turbinectomy. Statistical calculations were performed using the Kruskal–Wallis formula.The sample included 75 patients with an average age of 33.4 years, mostly female (51%; n = 38). The average ROE score in the sample was 79.6%. Thirty-eight point seven percent (n = 29) of the procedures were performed after nasal pyramid trauma, with these patients reporting higher ROE scores than others (85.78% in the trauma group; 75.6% in the nontrauma group; p-value = 0.01394). Even though no statistical correlation was demonstrated, ROE scores were also higher in patients with allergic rhinitis (82.1% vs. 78.1% on the healthy group), psychiatric disorders (85.8% vs. 75.6% on the healthy group), hematological disorders (91.7% vs. 78.9% on the healthy group), nonsmokers (81.7% vs. 74.0% on smokers), younger patients (81.7% vs. 76.8% on patients older than 33.4 years) and patients that underwent inferior turbinectomy (81.0% vs. 75.9%).This study established a correlation between the subjective degree of surgical satisfaction and previous nasal trauma in patients undergoing FRS.
Keywords: functional rhinoseptoplasty; rhinoplasty outcome evaluation; rhinoseptoplasty